2017
DOI: 10.1016/j.scitotenv.2016.10.238
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality in office buildings across Europe – The OFFICAIR study

Abstract: The European project OFFICAIR aimed to broaden the existing knowledge regarding indoor air quality (IAQ) in modern office buildings, i.e., recently built or refurbished buildings. Thirty-seven office buildings participated in the summer campaign (2012), and thirty-five participated in the winter campaign (2012-2013). Four rooms were investigated per building. The target pollutants were twelve volatile organic compounds, seven aldehydes, ozone, nitrogen dioxide and particulate matter with aerodynamic diameter <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 41 publications
6
94
5
3
Order By: Relevance
“…Moreover, the results for particulate matter for slightly toasted agree with the ones described by He et al [45] who reported a median PM 2.5 level of 35 µg·m −3 for the peak values, which are lower than the PM 2.5 levels of 62.6 ± 27.7 µg·m −3 and PM 10 levels of 125.6 ± 87.1 µg·m −3 found for the toasting bread experiment in controlled conditions [18]. Both levels of medium and heavily toasted bread contributed to concentrations above the limit values for CH 2 Particulate matter levels (both PM2.5 and PM10) during the frying process were significantly higher than the ones found during the boiling process in both dwellings. Moreover, the mean concentrations during the frying process were above the protection limit established by the Portuguese legislation [32] for all experimental conditions (gas or electricity, both dwellings) for both fractions (PM2.5 and PM10).…”
Section: Emissions From Toastingmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the results for particulate matter for slightly toasted agree with the ones described by He et al [45] who reported a median PM 2.5 level of 35 µg·m −3 for the peak values, which are lower than the PM 2.5 levels of 62.6 ± 27.7 µg·m −3 and PM 10 levels of 125.6 ± 87.1 µg·m −3 found for the toasting bread experiment in controlled conditions [18]. Both levels of medium and heavily toasted bread contributed to concentrations above the limit values for CH 2 Particulate matter levels (both PM2.5 and PM10) during the frying process were significantly higher than the ones found during the boiling process in both dwellings. Moreover, the mean concentrations during the frying process were above the protection limit established by the Portuguese legislation [32] for all experimental conditions (gas or electricity, both dwellings) for both fractions (PM2.5 and PM10).…”
Section: Emissions From Toastingmentioning
confidence: 80%
“…There has been extensive research on micro-environments where people spend their time with the aim of understanding exposure patterns. Initially, the studied micro-environments were mainly buildings in which people spend a significant fraction of the daytime such as offices [2,3], public buildings like schools [4][5][6], dwellings [7], and other indoor places where leisure activities [8][9][10] are developed. In recent years, the need to understand the exposure levels in an integrated perspective has started to gain consensus since individuals spend around 90% of their time in different indoor environments.…”
Section: Introductionmentioning
confidence: 99%
“…The research strategy consisted of three complementary phases: (a) “general survey” (167 buildings, winter of 2011‐2012), using questionnaires and checklists; (b) “detailed study” (37 buildings) with measurements carried out both in summer (2012) and winter (2012‐2013); and (c) “intervention study” (nine buildings) with more detailed measurements (eg, active sampling and online monitoring) carried out before and after an intervention related to the reduction in IAP. Further details on the project strategy and outcomes are reported in the project website (http://www.officair-project.eu) and in project‐related publications …”
Section: Methodsmentioning
confidence: 99%
“…During the field campaigns, some physical (temperature, relative humidity, and air change rate) and chemical parameters were measured; these last included particulate matter (PM 2.5 ), ozone (O 3 ), nitrogen dioxide (NO 2 ), aldehydes (formaldehyde, acetaldehyde, acrolein, propanal, benzaldehyde, glutaraldehyde, and hexanal), and VOCs (benzene, toluene, xylenes, ethylbenzene, n‐hexane, trichloroethylene (TCE), tetrachloroethylene (PCE), α‐pinene, d‐limonene, 2‐butoxyethanol, 2‐ethylhexanol, and styrene). The investigated IAPs were chosen based on a literature review of IAPs in office environments and on their potential association with health outcomes (eg, sensory irritation symptoms, cardiovascular and pulmonary effects) . Most of them are also known to be emitted from building materials, cleaning products, and office equipment …”
Section: Methodsmentioning
confidence: 99%
“…Serious health problems are related to sick building syndrome, which is usually associated with the quality of indoor air (Mullen et al, 2016;Mandin et al, 2017). In urban areas, most citizens have long-term exposure to large amounts of harmful chemicals indoors, whether it's at home or working at the office (Zheng et al, 2011;Shi et al, 2015;Lukcso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%